Life on the edge for the Indian dentist: A look at infection control and its application for Indian dental offices - Farias, Anand Francis; Rai, Sajni; Rao, Taru (International Journal of Infection Control, 2014)
Dental health personnel are constantly exposed to the potential threat of developing an infection by occupational exposures to a variety of microbial pathogens, most common of all are hepatitis B virus (HBV), hepatitis C (HCV) tuberculosis (TB) and acquired immunodeficiency syndrome. Literature has detailed how globally; private practices do not always follow all infection control procedure despite numerous guidelines and regulations being published. Cross infection control practices in Indian dental clinics are said to be years behind the guidelines prescribed by regulatory bodies in the Western World. Researchers have reported on the lax attitudes of dentists in India regarding management of biomedical wastes. This review attempts to assess the possible sources of infection in a clinic setup and relate them to a dental clinic setup in India, and provide the reader with an insight to implement and monitor infection control protocols in the Indian dental setup